Il concetto di controtransfert nella psicoanalisi da W. Bion fino a ogg - Salvador, Enrica; Battaglia, Claudia (Il sogno della farfalla, 2014)
The article examines the evolution of the concept of countertransference from the 50s to the present day, starting from the Kleinian concept of projective identification which follows, according to the authors, a “modified drive model” of the etiopathogenesis of psychic disorders and, subsequently, considers countertransference a technical mistake. Nevertheless, the Kleinian concept of projective identification invigorated the discussion on countertransference because it was the starting point of numerous studies on countertransference in the therapy of patients suffering from schizophrenic psychosis. In this regard, the article takes into examination the works of W. Bion and L. Grinberg, proceeding then to briefly consider contemporary psychoanalytic authors including O. Kernberg. Given the growing attention that the concept of countertransference is attracting within experimental research, the article ends with a discussion of some recent works that use rating scales in their attempt to classify and quantify countertransference.